using factor method divide x^2+3x+2 ÷ x+1
Answers
Answered by
24
Factorising the polynomial :-
so,
=
Hope it helps you
Thanks for asking....
@ Prabhudutt
Answered by
19
Answer :-
First,
=>![\bold{x^2\: +\: 3x\: +\: 2} \bold{x^2\: +\: 3x\: +\: 2}](https://tex.z-dn.net/?f=%5Cbold%7Bx%5E2%5C%3A+%2B%5C%3A+3x%5C%3A+%2B%5C%3A+2%7D)
=>![\bold{x^2\: +\: 2x\: +\: 1x\: +\: 2} \bold{x^2\: +\: 2x\: +\: 1x\: +\: 2}](https://tex.z-dn.net/?f=%5Cbold%7Bx%5E2%5C%3A+%2B%5C%3A+2x%5C%3A+%2B%5C%3A+1x%5C%3A+%2B%5C%3A+2%7D)
=>![\bold{x\: (x\: +\: 2)\: +\: 1\: (x\: +\: 2)} \bold{x\: (x\: +\: 2)\: +\: 1\: (x\: +\: 2)}](https://tex.z-dn.net/?f=%5Cbold%7Bx%5C%3A+%28x%5C%3A+%2B%5C%3A+2%29%5C%3A+%2B%5C%3A+1%5C%3A+%28x%5C%3A+%2B%5C%3A+2%29%7D)
=>![\bold{(x\: +\: 1)\: (x\: +\: 2)} \bold{(x\: +\: 1)\: (x\: +\: 2)}](https://tex.z-dn.net/?f=%5Cbold%7B%28x%5C%3A+%2B%5C%3A+1%29%5C%3A+%28x%5C%3A+%2B%5C%3A+2%29%7D)
Now,
=>![\bold{(x\: +\: 1)\: ( x\: +\: 2)/ (x\: +\: 1)} \bold{(x\: +\: 1)\: ( x\: +\: 2)/ (x\: +\: 1)}](https://tex.z-dn.net/?f=%5Cbold%7B%28x%5C%3A+%2B%5C%3A+1%29%5C%3A+%28+x%5C%3A+%2B%5C%3A+2%29%2F+%28x%5C%3A+%2B%5C%3A+1%29%7D)
=>![\bold{(x\: +\: 2)} \bold{(x\: +\: 2)}](https://tex.z-dn.net/?f=%5Cbold%7B%28x%5C%3A+%2B%5C%3A+2%29%7D)
So the answer is (x + 2)
First,
=>
=>
=>
=>
Now,
=>
=>
So the answer is (x + 2)
Similar questions